Sequential determination of viral load, humoral responses and phylogenetic analysis in fatal and non-fatal cases of Crimean-Congo hemorrhagic fever patients from Gujarat, India, 2019 - Sahay, Rima R.; Shete, Anita M.; Yadav, Pragya D.; Patil, Savita; Majumdar, Triparna; Jain, Rajlaxmi; Nyayanit, Dimpal A.; Kaushal, Himanshu; Panjwani, Sunil J.; Upadhyay, Kamlesh J.; Varevadiya, Chetan L.; Vora, Alpesh; et al. (PLoS neglected tropical diseases, 2021)
Background Thirty-four CCHF cases (17 fatal; 17 survived) were confirmed from Gujarat state, India during the year 2019. We aimed to find out the viral load, antibody kinetics, cytokine profile and phylogenetic analysis between fatal and non- fatal cases. Methods Thirty four cases were included in this study. Blood and urine samples were collected from all the cases on the day of admission to hospital. Non-fatal cases were followed weekly for understanding the profile of viral kinetics, anti-CCHFV IgM and IgG antibodies. We also quantified the cytokines in both fatal and non-fatal cases. For epidemiological correlation, livestock were screened for anti CCHF IgG antibodies and the tick pool specimens were tested by real time RT-PCR. Virus isolation was attempted on tickpools and human specimens and phylogenetic analysis performed on human and ticks complete genome sequences. Results CCHF cases were detected throughout year in 2019 with the peak in August. Out of 34 cases, eight secondary CCHF cases were reported. Cases were predominantly detected in males and in 19-45 years age group (55.88%). The persistence of viremia was observed till 76.sup.th POD in one case whereas anti-CCHFV IgM and IgG was detected amongst these cases from the 2.sup.nd and 20.sup.th POD (post onset date) respectively. Positivity observed amongst livestock and tick pools were was 21.57% and 7.4% respectively. The cytokine analysis revealed a significant increase in the level of serum IL-6, IL-10 and IFN-[gamma] during the acute phase of the infection, but interestingly IL-10 lowered to normal upon clearance of the virus in the clinically recovered case. Fatal cases had high viral RNA copy numbers. Bleeding from one or two mucosal sites was significantly associated with fatality (OR-16.47;p-0.0034 at 95% CI). We could do CCHF virus isolation from two cases. Phylogenetic analysis revealed circulation of re-assortment of Asian-West African genotypes in humans and ticks. Conclusions The persistence of CCHF viral RNA was detected till 76.sup.th POD in one of the survivors. The circulation of a re-assortment Asian-West African genotype in a CCHF case is also reported first time from India.